Improving the machinability of the high-entropy alloy CoCrFeMnNi by in-situ laser-assisted diamond turning - Hanheng Du; Yidan Wang; Yuhan Li; Sen Yin; Denghui Li; Wai Sze Yip; Suet To (Journal of Materials Research and Technology, 2023)
High-entropy alloys, as the novel multi-principal alloys composed of five or more elements in equal-atomic ratios or near-equal atomic ratios, are widespread in extreme environments, including high-temperature, high-dynamic loading, and high-irradiation. However, how to improve their machinability still faces challenges because of their high hardness and wear resistance. To solve this problem, this paper proposes an in-situ laser-assisted diamond turning process. Experimental results show the machinability of the high-entropy alloy CoCrFeMnNi is obviously improved. The average value of the surface roughness Sa of the machined sample reaches 2 nm. Compared with the traditional single-point diamond turning, the surface quality is improved by 33.3 %, demonstrating the effectiveness of the proposed machining method. Tool wear also decreases by above 35 %, again demonstrating the superiority of the proposed machining method. Besides, the effect of the machining on the crystalline structure is also analyzed. Therefore, this study provides an efficient and simple approach for enhancing the machinability of the high-entropy alloy CoCrFeMnNi, which can be applied in industrial production in the future.